(untitled) (Psicologia USP, 2006)
In this reserch we did an institutional analyses, which aims is to examine the catholic ecclesiastical formation practices by means of institutional functioning from a catholic seminary and the register of the ecclesiastical knowledge, producer of a specific subjectivity pattern (future priests). By observing the everyday of that establishment, the semi-structured interviews with institution actors, the analyses of official documents of the catholic Ministry and relevant literature, we looked for understanding the formation relationship between priests responsible for the formation and seminarians concerning to a privileged and constitutive device of the seminary as an agent producer of subjectivity. Thus we come to the conclusion that the seminary focused can be considered as a common disciplinary institution, which maintains the report as its main mechanism and microphysics device (exam tool, surveillance and normal process sanction).